1964
DOI: 10.1007/bf02661407
|View full text |Cite
|
Sign up to set email alerts
|

A neutron activation method for soil removal measurements: A comparison of the reflectance method and the neutron activation method

Abstract: A nondestructive neutron activation analysis technique has been developed to determine the amt of particulate kaolinite clay soil removed from cotton fibers during a wash cycle. Neutron bombardment of aluminum, present as a constituent of the kaolinite lattice structure, produces short‐lived aluminum‐28. The amt of particulate soil present on a piece of cotton cloth before and after the wash cycle is determined by े scintillation counting of the aluminum‐28, thus providing an absolute method for the determinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

1974
1974
1998
1998

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…Total clay analysis by neutron activation. Neutron activation analysis was used to provide a quantitative measure of the amount of residual particulate soil present on the fabric (11). Specimens were activated at the Ward Nuclear Laboratory at Cornell University, using the Rabbit Facility.…”
Section: Sk Obendorfmentioning
confidence: 99%
“…Total clay analysis by neutron activation. Neutron activation analysis was used to provide a quantitative measure of the amount of residual particulate soil present on the fabric (11). Specimens were activated at the Ward Nuclear Laboratory at Cornell University, using the Rabbit Facility.…”
Section: Sk Obendorfmentioning
confidence: 99%
“…Neutron activation analysis (NAA) is a recognized analytical method for determining the amount of clay soil removed from fabric during a wash cycle (1,2,5). Netzel et al (6) first reported this method for determining the amount of kaolinite clay soil present on cotton cloth before and after washing by gamma scintillation counting of the 28 Al.…”
mentioning
confidence: 99%
“…, Recently a radioactive tracet technique ~37,44,45,77,117) has been employed for determining the amount t of soil,deposited or released from the fabric surface. By determining the amount of radioactive soil present, one can calculate the degree of soiling or soil release.…”
mentioning
confidence: 99%